An ecological approach to understanding Women's reproductive health and pregnancy decision making in Greenland. (September 2022) - Rink, Elizabeth; Anastario, Mike; Reimer, Gitte Adler; Peterson, Malory
Abstract: Using a community based participatory research framework and ecological systems theory we explored the experiences of reproductive health among Inuit women living in a remote Northwestern settlement in Greenland to understand the multiple diverse factors that influence their pregnancy outcomes. We conducted 15 in depth interviews with Inuit women between the ages of 19 and 45. Key factors influencing women's pregnancy decision making were: 1) precursors to pregnancy; 2) birth control use; 3) adoption and abortion; and 4) access to reproductive health care. Our results highlight the need to identify pathways through research, policy, health promotion, and health care practice that can support Inuit women in Greenland to be reproductively healthy and make informed decisions about pregnancy that resonate with their cultural beliefs as well as the realities of their everyday lives. We recommend the integration of cultural messaging into interdisciplinary approaches for preventive reproductive health care with women living in remote Arctic communities. Highlights: Greenlandic Inuit communities need access to culturally congruent methods of contraception and reproductive healthcare. Intrafamilial narratives heavily influence individual pregnancy outcomes for Greenlandic Inuit women. Greenlandic governmental policies support abortion with a need to strengthen pregnancy prevention strategies.